Modern approaches to radiotherapy in primary cutaneous lymphomas: insights and recommendations from the DEGRO dermato-oncology working group - Elsayad, Khaled; Correia, Dora; Theiß, Ulrike; Baehr, Andrea; Besserer, Angela; Micke, Oliver; Greve, Burkhard; Waldstein, Cora; Corradini, Stefanie; Habermehl, Daniel; König, Laila; Hering, Kathrin; et al. (Strahlentherapie und Onkologie, 2025)
The growing use of reduced-dose radiotherapy in patients with primary cutaneous lymphoma is a promising development. Nevertheless, the absence of controlled clinical trials to ascertain standardized doses for each specific type constitutes a significant impediment to the advancement of this field. This expert opinion strongly advocates for advancements in radiation oncology practice that address the unique complexities of primary cutaneous lymphoma. By refining our methodologies, we can optimize patient care and outcomes in this dynamic field.
Online verfügbar: 09. September 2025
Gesehen am 03.02.2026